A Betulinic Acid Derivative, BA5, Induces G0/G1 Cell Arrest, Apoptosis Like-Death, and Morphological Alterations in Leishmania sp - Magalhães, Tatiana Barbosa dos Santos; Silva, Dahara Keyse Carvalho; Teixeira, Jessica da Silva; De Lima, Juliana Dizaira Teles; Barbosa-Filho, José Maria; Moreira, Diogo Rodrigo Magalhães; Guimarães, Elisalva Teixeira; Soares, Milena Botelho Pereira (Frontiers in Pharmacology, 2022)
Leishmaniases are endemic diseases caused by different species of intracellular parasites of the genus Leishmania. Due to the high toxicity and drug resistance of current antileishmanial drugs, it is necessary to identify new and more effective drugs. Previously, we investigated the immunomodulatory and anti-Trypanosoma cruzi action of BA5, a derivative of betulinic acid. In the present study, we investigated the in vitro activity of BA5 against different species of Leishmania and their action mechanism. BA5 exhibited low cytotoxicity against macrophages and inhibited the proliferation of promastigote forms of Leishmania amazonensis (IC50 = 4.5 ± 1.1 μM), Leishmania major (IC50 = 3.0 ± 0.8 μM), Leishmania braziliensis (IC50 = 0.9 ± 1.1 μM) and Leishmania infantum (IC50 = 0.15 ± 0.05 μM). Incubation with BA5 reduced the percentage of Leishmania amazonensis-infected macrophages and the number of intracellular parasites (IC50 = 4.1 ± 0.7 μM). To understand the mechanism of action underlying BA5 antileishmanial activity (incubation at IC50/2, IC50 or 2xIC50 values of the drug), we investigated ultrastructural changes by scanning electron microscopy and evaluated cell cycle, membrane mitochondrial potential, and cell death against promastigote of Leishmania amazonensis by flow cytometry. Promastigotes incubated with BA5 presented membrane blebbing, flagella damage, increased size, and body deformation. Flow cytometry analysis showed that parasite death is mainly caused by apoptosis-like death, arrested cell cycle in G0/G1 phase and did not alter the membrane mitochondrial potential of Leishmania amazonensis. Surprisingly, the combination of BA5 and amphotericin B, a assay used to determine the degree of drug interaction, revealed synergistic effects (CI=0.15 ± 0.09) on promastigotes forms of Leishmania amazonensis. In conclusion, BA5 compound is an effective and selective antileishmanial agent.